Particleboards from CCB-Treated Pinus sp. Wastes and Castor Oil Resin: Morphology Analyses and Physical-Mechanical Properties - Bertolini, Marilia Da Silva [UNESP]; Galvaõ De Morais, César Augusto [UNESP]; Lahr, Francisco Antônio Rocco; Freire, Rodrigo Teixeira Santos; Panzera, Túlio Hallak; Christoforo, André Luis (American Society of Civil Engineers (ASCE), 2019)
This work evaluated the use of Pinus sp. wastes treated with a chromium, copper and boron compound (CCB), a wood preservative, to fabricate particleboards based on castor oil-polyurethane resin. The effects of wood particle content, resin mass fraction, pressing time, and their interactions on the physical (thickness swelling, moisture content, water absorption, and density) and mechanical properties (internal bond, and edge and face screw-holding capacity) were evaluated via full factorial design and ANOVA. Two experimental conditions resulted in mechanical properties which meet or surpass the standard requirements and were therefore selected for porosimetric and microscopic analyses. Retention of CCB active ingredients was determined (for particles and particleboards) in order to evaluate possible volatilization during manufacture. The results showed that after a 7.7% increase in wood particle content, the thickness swelling after 2 h decreased by 16.5% and water absorption after 2 h (24 h) decreased by 17.4% (25.3%). In contrast, the moisture content increased by 5.9%. On the other hand, the 25% increase in resin mass fraction resulted in 22.1% and 19% reductions in thickness swelling after 2 and 24 h, respectively. Water absorption after 24 h also decreased by 20.7%. In contrast, internal bond increased by 13.8% with a 25% increase in resin mass fraction. The interaction of factors was not significant for the studied properties. In particular, the factors considered did not significantly affect the screw-holding capacity response. The decrease in active ingredients of the preservative was linked to mass balance by taking into consideration the amount of resin in the composition of the panels.
Keywords: Castor oil-based polyurethane adhesive; Morphology; Particleboard; Physico-mechanical properties; Treated-wood wastes